The effect of Rosenberg’s model on developing sensory-kinesthetic perception of the skills of chest handling and jumping from spinning basketball for students - Ali Dawood, Rafid (International Journal of Psychosocial Rehabilitation, 2020)
The design of teaching is very important for the process of teaching because it determines the educational goals and regulates the stages of the process. It also identifies most models suitable and appropriate and in line for the goals and implementation can also be judged on the success of the design process whether or not through the organization of parts composing them, the stages of design Altders include at Rosenberg five stages Which includes comprehensive analysis, design, development and production, implementation, and evaluation. Rosenberg believes that these four stages are the first stage, as they help in identifying a problem by identifying the necessary needs and converting them into useful information to extend the process of teaching and training. care about the characteristics of the learner and the characteristics of teaching aids and learning standards attitudes are also interested in the development stage Pthoude t necessary educational materials and teaching aids accompanying the presentation of the material by the lessons, or trainers and then the implementation phase of the skill, while the second phase includes the final phase of the form, a calendar, and linked to a basketball game with a number of Sensory perceptions (sensory - kinesthetic) that can be developed and developed in training, the most important of which is perceiving a sense of distance, time and place, as well as a sense of the ball Noting the motor rhythm umbilical p in the formations of attack rapidly, which necessitated the availability of physical and skill and major tactical capabilities must be data owned by the player in line with contrasting fast performance in the competitions and comes of the capabilities through continuous hard training, especially the capabilities of cognitive sense-kinetic and no less important than others capacity, and through the follow - up to the researcher to perform Mhar T - handling chest with both hands and shooting by jumping from the rotation of the students noted weakness in the performance of a, for several reasons, it may be including the lack of use of models so many featured models of different teaching which provided an opportunity to choose the style appropriate to the nature and circumstances educated environment to be able to achieve its goals and educational work on the learners ’ abilities and development of development, hence the problem is therefore considered a researcher statement impact of a specimen Rosenberg in the development of cognitive sense - dynamic to the skills of handling thoracic and correction by jumping from a spinning reel basketball for students, either target research they know the effect of a specimen Rosenberg in developing sensory-kinesthetic perception of the skills of chest handling and2 shooting from spinning in basketball for students, and the researcher hypothesized that there are differences Statistically significant between desorption experimental and control two groups of tribal tests and dimensionality for the benefit of posteriori tests, as well as the existence of significant differences significant between the desorption two groups in the post tests for the benefit of the experimental group.